THE ROLE OF THE TEACHER AS AN INNOVATOR IN GROWING LANGUAGE SKILLS STUDENT IN THE 21ST CENTURY - Reksa Adya Pribadi; Lulu Damayanty; Siti Meiliana Syahra Iswandi (Institut Pendidikan Indonesia, 2023)
In the current era of globalization, interactions with other individuals are unlimited. The interactions that occur even allow a person to be able to communicate with citizens around the world, therefore communication skills and confidence when communicating are needed. One way to instill confidence in using English is to hold a bilingual program at school. This study aims to describe the teacher's role in cultivating language skills, innovations made by teachers in cultivating language skills, and describing students' language skills at school. Collecting data in this study used a qualitative approach with descriptive methods, where the data collection used interview, observation and documentation techniques. The results of this study indicate that with this bilingual activity, educators need to develop foreign language skills well and have the confidence they have. From the research results obtained by researchers, it shows that there is an increase in foreign language proficiency and a sense of self-confidence in educators.